1978
DOI: 10.1136/jcp.31.5.488
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and fibrinolytic activity of cerebrospinal fluid.

Abstract: SUMMARY Fibrin/fibrinogen degradation products (fragments D and E) were detected in cerebrospinal fluid in 23'4% of 252 patients admitted to a neurological/neurosurgical unit. Other coagulation proteins of low molecular weight (plasminogen and factor IX) were also present but larger proteins (fibrinogen and factor V) were not. These findings are consistent with protein leakage across a blood-CSF barrier damaged by inflammatory, vascular, or neoplastic disease. Fibrin/ fibrinogen degradation products in cerebro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…PA in CSF, measured on fibrin plates, was rarely detected and was uninfluenced by antifibrinolytic therapy. Anderson et al 4 found an increased PA in CSF in only one of four patients, and FDP in CSF in ten patients studied within 96 hours of the initial SAH. We found an increase in local fibrinolysis in CSF as measured on unheated fibrin plates as well as with increased levels of FDP.…”
Section: Discussionmentioning
confidence: 97%
“…PA in CSF, measured on fibrin plates, was rarely detected and was uninfluenced by antifibrinolytic therapy. Anderson et al 4 found an increased PA in CSF in only one of four patients, and FDP in CSF in ten patients studied within 96 hours of the initial SAH. We found an increase in local fibrinolysis in CSF as measured on unheated fibrin plates as well as with increased levels of FDP.…”
Section: Discussionmentioning
confidence: 97%
“…24 Anderson et al24 found that FDPs were accompanied by other low molecular weight coagulation proteins but not the heavier ones. They believe that this indicates an origin from leakage across the blood-brain barrier and not from lysis within the subarachnoid space.…”
Section: Discussionmentioning
confidence: 99%
“…The source of the FDP found in the CSF of patients with meningitis is not known. They are not found in normal CSF but have been detected in the CSF of patients with a wide variety of noninfective neurological conditions (Brueton et al, 1976;Anderson et al, 1978). The presence of FDP, and other low molecular weight proteins, in the CSF of these patients is thought to follow their leakage from the plasma across a damaged blood-brain barrier (Anderson et al, 1978).…”
Section: Discussionmentioning
confidence: 99%